Laurel Leaves: Special Edition A Checklist and Purchase Guide for School and Community Libraries in Appalachia - Miller, Jim Wayne (Appalachian State University, 1978)
Published in 1979, this publication was written to help combat the misinformation, myth, and stereotypes of the Appalachian region. Miller's intention was to publish an intuitive guide for teachers highlighting new literature on the Appalachian region.